PENGARUH KONTEN PESAN "SEX EDUCATION" INSTAGRAM @TABU.ID TERHADAP KEPUASAN FOLLOWERS (Survei pada Pengikut Akun Instagram @tabu.id) - Nabilla Thalita Fadis (2022)
In Indonesia the information about sex very low, sources of information that people get from social media about sex education can influence sexual behavior. Instagram @tabu.id is present as a source of information and discussion forum for teenagers related to sexual and reproductive health, because the teenagers are still often wrong in making decisions. Content message Instagram @tabu.id about sexual and reproductive education can fulfill teenagers' knowledge about sex. The purpose of the research is to find out how much the effect on influence of tabu.id "sex education" message content Instagram on followers satisfaction as a social media user. The relevan theory of this research is the Uses and Gratifications Theory, this theory explains that people are active and able to study or evaluate various types of media by looking at how users choose the media that can be trusted to meet their needs and the extent to which users are satisfied with what is presented by the media. This research are using quantitative method. The research method in this study is the survey method. The population of this research are @tabu.id Instagram account followers with 100 respondent. In analyzing data, the researcher conducted validity and reliability tests, correlation tests, simple linear regression tests, coefficient of determination, and hypothesis testing. The data testing technique is processed using the SPSS (Statistical Product and Service Solution) version 25 program. The results showed that there was a strong relationship between Influence of @tabu.id "sex education" Message Content Instagram on followers satisfaction with a correlation value of 0,731. The coefficient of determination shows that the effect on Influence of @tabu.id "sex education" message content Instagram on followers satisfaction is 52,7% and the rest is influenced by other factors. This result is strengthened by the results of hypothesis testing which states that Ho is rejected and Ha is accepted, which means that there is a significant effect on Influence of @tabu.id "sex education" message content Instagram on followers satisfaction. The conclusion of this study is that there is a strong influence between message content on followers satisfaction as social media user. Researchers hope that further research can find out more about other factors that can affect the audience to get media use satisfication.